Study of some properties of hydrophilic ointment bases depending on their composition - Lyapunov, Nikolay; Bezugla, Olena; Liapunova, Anna; Zinchenko, Igor; Liapunov, Oleksii; Lysokobylka, Oleksii; Dzhoraieva, Svitlana (ScienceRise: Pharmaceutical Science, 2025)
The aim. To study the properties of multicomponent hydrophilic ointment bases. Materials and methods. The study focused on hydrophilic bases with varying formulations and ointments containing ofloxacin. The rheological properties of the bases were studied using rotational viscometry, and water absorption and ofloxacin release were investigated using diffusion through a semipermeable membrane. The water content was determined by the semi-micro method, and the ofloxacin content was determined by liquid chromatography. Four spin probes were utilized in the experiment, and the EPR spectra of these spin probes in a mixed solvent PG – M400 and bases were obtained. The type and parameters of the EPR spectra were evaluated. Surface tension was measured using the maximum bubble pressure method, and antibacterial activity was assessed by the agar diffusion method. Results. The rheological parameters of hydrophilic bases are contingent on the ratio between macrogol 1550 (M1500) and poloxamer P338 (P338), as well as between macrogol 400 M400 and propylene glycol (PG), water content, temperature, and shear stress. It was demonstrated that P338 increases the surface-active properties of bases. The water absorption capacity of the base containing solely a mixture of macrogols is approximately 1.2 times higher than that of the base, which also contains P338 and PG. The release rate of ofloxacin is shown to increase with an increase in PG content, but it is unaffected by the replacement of Proxanol 268 with P338. The incorporation of macrogol 20 cetostearyl ether (M20CSE) and cetostearyl alcohol (CSA) markedly retards water absorption and the release of ofloxacin, and also increases the rheological parameters of the bases. It was demonstrated by the spin probe method that, within a non-aqueous medium, no aggregates are formed from molecules of P338, as well as surfactant and CSA molecules. The PG content affects the growth inhibition zones of P. aeruginosa. The antibacterial efficacy of ointments containing fluoroquinolones against resistant clinical bacterial strains was found to be enhanced by hydrophilic bases. Conclusions. The rheological parameters of hydrophilic bases can be controlled by modifying the ratio between consistency factors and dispersion medium components, by varying water content, temperature, and shear stress, as well as by adding surfactants and CSA to their formulations. Hydrophilic bases are able to absorb water and they promote the release of ofloxacin. Surfactant and CSA have a significant impact on these processes, reducing their rates. The formation of aggregates from P338 molecules, as well as molecules of surface-active substance and CSA, was not observed in the hydrophilic bases. PG, when incorporated into hydrophilic ointments containing ofloxacin, enhances their antibacterial efficacy